2001
DOI: 10.21225/d5hw2g
|View full text |Cite
|
Sign up to set email alerts
|

The Roller Coaster Life of the Online Learner: How Distance Educators Can Help Students Cope

Abstract: This paper describes a study of how one small group of graduate students coped with the stresses of learning at a distance over the course of the three to five years in which they were enrolled in their program of study. The study used a model of transition to examine how their coping responses changed as they moved into, through, and out of their program. It also assessed the students' perceptions of the "adult student friendliness" of the educational institution offering the program. The findings portrayed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, the findings coupled with in-class observations also suggest the strategy of flipped learning integrated with digital technologies such as the LMS can present a substantial learning curve. Wiesenberg (2013) observes the need for educators to be aware of, and provide resources for, addressing the challenges and stresses of online education. Similarly, in flipped classrooms utilising digital technology, attention needs to be given to strategies for shepherding students through the initial learning curve to help them adapt rapidly until these emergent forms of teaching and learning have become more prevalent in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings coupled with in-class observations also suggest the strategy of flipped learning integrated with digital technologies such as the LMS can present a substantial learning curve. Wiesenberg (2013) observes the need for educators to be aware of, and provide resources for, addressing the challenges and stresses of online education. Similarly, in flipped classrooms utilising digital technology, attention needs to be given to strategies for shepherding students through the initial learning curve to help them adapt rapidly until these emergent forms of teaching and learning have become more prevalent in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…The small, dated body of research about online advising states that a good online advisor responds to the needs and competing demands of students (Granger & Benke, 1998;Wiesenberg, 2001), assists in identifying resources, helps set an academic plan, supports students coping with distance education, adds to students' online study skills, sets shortterm immediate goals, encourages personal evalu ation (Granger & Benke, 1998;Ludwig-Hardman & Dunlap, 2003), demonstrates familiarity with various computer software and advising media, and offers career counseling (Granger & Benke, 1998). They also had been trained specifically on ways to advise online learners (Beaudoin, 1990;Granger & Benke, 1998;Wiesenberg, 2001).…”
Section: Advising the Adult Learnermentioning
confidence: 99%
“…Furthermore, the literature addressing online study primarily emphasizes the role of instructors over advisors, and cohort advising has been directed at the cohort members' largely recognized reliance on one another over a univer sity appointed advisor. In addition, many university policy makers have inaccurately assumed that adult or graduate learners do not require as much advising as do traditional-aged undergraduates (Merriam, Caffarella, & Baumgartner, 2007;Potthoff, Dinsmore, & Moore, 2001;Wiesenberg, 2001).…”
mentioning
confidence: 99%
“…Research with diverse cohorts of students has found students use a rollercoaster metaphor to illustrate the highs and lows of their first year (Kahu et al, 2015;Luzeckyj et al, 2017;Morrison-Saunders et al, 2010;Wiesenberg, 2001). The lows of the rollercoaster reflect the stress students experience, caused by a range of factors such as academic demands, procrastination and finances (Stallman and Hurst, 2016).…”
mentioning
confidence: 99%